Diagnosis dan Tata Laksana Mild Cognitive Impairment (MCI) - Celine Anindytha Pranata (PT Dexa Medica, 2024)
The number of elderly population in the world is increasing nowadays. In 2020, there were 1.4 billion people in the world aged ≥60 years and it is predicted to double by 2050. Decline in cognitive function and memory is one of the consequences of the aging process that can affect a person’s quality of life. MCI is a pathological condition also preclinical and transitional stage between normal aging and dementia. Early detection and intervention of MCI may delay onset and prevent the progressivity of MCI to dementia. This article aims to provide an overview of MCI which includes risk factors, subjective and objective clinical signs, disease course, diagnosis, and recommendation of MCI management based on existing studies and guidelines.